Konsep Kepemilikan Dalam Ekonomi Islam Menurut Taqiyuddin An-Nabhani - Nanang Sobarna (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2021)
This study aims to unravel Taqiyuddin An-Nabhani's thoughts on the concept of ownership in Islam. The research method used is a literature study, namely the source of data obtained from the results of a review of the literature in accordance with the problem. Meanwhile, in data collection, the writer uses analytical descriptive method by collecting data and reviewing and reviewing various sources of writing that have relevance to this research for further analysis. The concept of ownership in Islam according to Taqiyuddin An-Nabhani's view has a different concept from other economic systems. According to the Islamic economic system, property ownership in terms of quantity (quantity) is not limited but is limited by certain ways (quality) in obtaining property (there are halal and haram rules). In the Capitalist Economic System, the amount (quantity) of individual property ownership and the way to obtain it (quality) is not limited, that is, it is permissible in any way as long as it does not interfere with the freedom of others. In the socialist economic system, there is no private property. There is only state property which is distributed equally to all individuals in society. In contrast to the Islamic economic system, which has the view that there is individual ownership (private property), public ownership (public property) and state property (state property). According to the Islamic Economic System, the general type of ownership in particular should not be converted into state ownership or individual ownership.